Initial testing (stage 1) of M6620 (formerly VX‐970), a novel ATR inhibitor, alone and combined with cisplatin and melphalan, by the Pediatric Preclinical Testing Program. Issue 2 (17th September 2017) - Kurmasheva, Raushan T.; Kurmashev, Dias; Reynolds, C. Patrick; Kang, Min; Wu, Jianwrong; Houghton, Peter J.; Smith, Malcolm A.
Abstract: Background: M6620 is a novel inhibitor of the DNA damage repair enzyme ATR, and has potentiated the activity of cisplatin and irinotecan in non‐small cell lung cancer and colon cancer xenografts, respectively. Procedures: M6620 was tested in vitro at concentrations ranging from 1.0 nM to 10.0 μM and at 75 nM in combination with cisplatin or melphalan. M6620 was tested against 24 solid tumor xenografts alone and in combination with cisplatin. Cisplatin was administered intraperitoneally on days 1 and 8 at a dose of 5 mg/kg. M6620 was administered intravenously on days 2 and 9 at 20 mg/m 2 approximately 16 hr after cisplatin. Results: The median relative IC50 (rIC50 ) value for M6620 was 0.19 μM (range 0.03–1.38 μM). M6620 reduced the mean IC50 of cisplatin and melphalan by 1.48‐ and 1.95‐fold, respectively. M6620 as a single agent in vivo induced significant differences in event‐free survival (EFS) distribution in 5 of 24 (21%) solid tumor xenografts, but induced no objective responses. Cisplatin as a single agent induced significant differences in EFS distribution compared to control in 18 of 24 (75%) solid tumor xenografts. Three objective responses to cisplatin were observed. The M6620 and cisplatin combination induced significant differences in EFS distribution compared to control in 21 of 24 (88%), with four objective responses. Conclusions: M6620 showed modest potentiation of cisplatin and melphalan activity for some cell lines. M6620 showed little single‐agent activity and the addition of M6620 to cisplatin significantly prolonged time to event for a minority of tested xenografts across several histologies.